Effective Assessment of Generic Skills in Uganda's Secondary Schools - Joyce, Bukirwa Rebecca (East African Journal of Arts and Social Sciences, 2025)
The curriculum for each level of education in Uganda is clear and sequenced to cater for the learners' needs that embrace it. However, many products of this curriculum fall short of the labour market expectations because school leavers lack the competencies compatible with the 21st century. A multitude of educationists in Uganda have emphasized the need to develop 21st-century skills as the main focus of the education system. Indeed, the National Curriculum Development Center has integrated these skills into the lower secondary education curriculum and has particularly referred to them as generic skills. This study aimed at the effective assessment of generic skills in Uganda’s secondary schools. The objectives of the study included; highlighting the key generic skills needed in Uganda’s schools as emphasized in the lower secondary education curriculum; suggesting effective ways of assessing generic skills and identifying the challenges of assessing generic skills. Narrative literature review method was adopted and content analysis of peer-reviewed articles was used. In content analysis, themes in tandem with the objectives were used to present data, making it possible to interpret the results as the researcher reflected on the informants’ statements on the subject. The study revealed that the lower secondary education curriculum provides the learners with generic skills that include critical thinking and problem-solving; creativity and Innovation; communication, Cooperation and self-directed learning; and Numeracy and ICT. These skills are embedded in the subject syllabuses and teachers are expected to assess them using the learning outcomes. Formative assessment and summative assessment are carried out by individual teachers and UNEB respectively. Challenges exist in assessing a large number of learners by individual subject teachers and yet some teachers lack the competencies to be assessed. Most teachers and parents prefer the traditional methods of assessment. The study concluded and stressed the urgent need for a paradigm shift from current assessment strategies to those techniques that promote the assessment of generic skills specifically. The study recommended teachers become mentors to support the development of these skills in the learners; introduce peer mentors from among senior students; and conduct peer assessment and self-assessment in addition to teacher assessment. A panel of three teachers was recommended to assess each student on generic skills at a summative level to reduce subjectivity in assessment.